2017
DOI: 10.1111/apt.14119
|View full text |Cite
|
Sign up to set email alerts
|

Significant positive association of endotoxemia with histological severity in 237 patients with non‐alcoholic fatty liver disease

Abstract: Endotoxemia is positively associated with NASH and significant fibrosis. The association between TM6SF2 and endotoxemia warrants further investigations. The findings may shed light on the pathogenesis of NASH and inform a novel treatment target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 50 publications
3
48
0
4
Order By: Relevance
“…Interestingly, TM6SF2 has been implicated in cholesterol synthesis . In addition, TM6SF2 , but not PNPLA3 , genotypes correlate with endotoxemia . Hence, the lean NAFLD phenotype might be consistent with obesity resistance, in which individuals are still prone to develop steatosis in response to an obesogenic environment (and perhaps a diet enriched in cholesterol), likely by genetic and gut‐driven mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TM6SF2 has been implicated in cholesterol synthesis . In addition, TM6SF2 , but not PNPLA3 , genotypes correlate with endotoxemia . Hence, the lean NAFLD phenotype might be consistent with obesity resistance, in which individuals are still prone to develop steatosis in response to an obesogenic environment (and perhaps a diet enriched in cholesterol), likely by genetic and gut‐driven mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the successful pharmacological inhibition of hepatic monocyte/macrophage infiltration and amelioration of steatosis and inflammation development by the inhibition of Ccl2 or Cxcl10 , which links hepatocyte lipotoxicity to macrophage‐associated liver inflammation in NASH as a potent chemotactic ligand . There is evidence that the endotoxemia marker Lbp is increased in patients with NASH and this correlates with lobular inflammation, and the knockout of Lbp in mice can decrease indices of liver damage determined by liver histology and serum transaminases . Stat1 serves as a mediator in interferon γ and chemokine expression induced by lipopolysaccharide in macrophages, and the inhibition of Stat1 can inhibit the release of chemokines and suppress the amplification cascade of inflammatory signals .…”
Section: Discussionmentioning
confidence: 99%
“…35 Studies have demonstrated the successful pharmacological inhibition of hepatic monocyte/macrophage infiltration and amelioration of steatosis and inflammation development by the inhibition of Ccl2 or Cxcl10, which links hepatocyte lipotoxicity to macrophage-associated liver inflammation in NASH as a potent chemotactic ligand. 36,37 There is evidence that the endotoxemia marker Lbp is increased in patients with NASH and this correlates with lobular inflammation, 38 There were some limitations to our study. First, TG levels were measured only in the serum, while its accumulation in hepatocytes is actually the main component of hepatic steatosis.…”
Section: Network-based Regulatory Model Of Yzh Liquid On Nashmentioning
confidence: 92%
“…NASH is now the most common indication for liver transplant in the Western world. NASH with advanced fibrosis is associated with a faecal microbiome‐derived metagenomic signature 50 and increased endotoxaemia 51 …”
Section: Microbiota In Liver Diseasementioning
confidence: 99%
“…NASH with advanced fibrosis is associated with a faecal microbiome-derived metagenomic signature 50 and increased endotoxaemia. 51 The gut microbiota may also play a role in the variable susceptibility to alcoholic liver disease. The microbiota differs between patients with severe alcoholic hepatitis and those who maintain normal hepatic function despite similar alcohol intake.…”
Section: Microbiota Role In Obesity and The Metabolic Syndromementioning
confidence: 99%